The Estimated Economic Burden of Cancers Attributable to Suboptimal Diet in the United States (OR17-03-19). (13th June 2019) - Khushalani, Jaya; Cudhea, Frederick; Ekwueme, Donatus; Harris, Diane; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract: Objectives: Suboptimal diet has been estimated as a major preventable cost of cancer. We aimed to quantify the 5-year direct medical costs for the estimated proportion of cancers attributed to suboptimal consumption of 7 dietary factors (fruits, vegetables, whole grains, processed meats, red meats, sodium, and sugar-sweetened beverages) among US adults. Methods: A Comparative Risk Assessment model was used to estimate the population attributable fractions (PAFs) for each diet-cancer pair and joint PAFs for 15 cancers. A Markov cohort model with Monte Carlo simulations was used to compute 5-year cancer costs attributable to suboptimal diet using PAFs, phase-specific costs of cancer care, and probability of death. Data inputs include national dietary data from the 2011–14 National Health and Nutrition Examination Survey (NHANES), optimal intake from the Global Burden of Disease (GBD) estimates, cancer incidence and survival from the Surveillance, Epidemiology, and End Results (SEER) program, and phase-specific costs of cancer care and projections from published literature. Results: The estimated 5-year direct medical cost of 15 cancers attributed to 7 dietary factors was 4.5 billion (95% uncertainty interval [UI]: 4.3-4.8). Largest costs (82%) were from colorectal cancer (2.8 billion, 95% UI: 2.6-3.0), and due to consumption of insufficient whole grains (1.9 billion, 95% UI: 1.7-2.1) and excess processed meat (1.1 billion, 95% UI: 1.0-1.3). Total estimated 5-year direct medical costs for cancer attributable to other dietary factors included 0.8 and 0.5 billion for insufficient vegetable and fruit consumption, respectively and 0.4, 0.2 and 0.2 billion for high intake of red meat, sodium and sugar-sweetened beverages, respectively. Conclusions: These novel findings highlight the opportunity to reduce cancer and associated costs via nutritional policies for the primary prevention of cancer. The results can also inform and serve as inputs for economic evaluation and design and testing of diet-related interventions to prevent cancer in the U.S. Funding Sources: None. Supporting Tables, Images and/or Graphs: